Religious Time and Symbolic Hegemony: An Analysis of National Holiday Policy in Indonesia - Muhammad Nasir; Dwi Wahyuni (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
This article examines the national holiday and collective leave policies in Indonesia as a practice of the religious time that reflects the relationship between the state, religion, and the formation of collective memory. Through a thematic content analysis of the Joint Decree of Three Ministers concerning National Holidays and Collective Leave for the 2020–2025 period, the article demonstrates that the regulation of public time is not merely an administrative instrument but also an arena of symbolic hegemonization representing the dominance of the majority religion. The study employs a qualitative approach based on document analysis, specifically Thematic Content Analysis to uncover patterns of representation, symbolic hierarchies, and the state's construction of religious time. Drawing on Maurice Halbwachs’s perspective on collective memory, Murray Edelman’s symbolic politics, and William E. Connolly’s critique of state neutrality regarding religious representation, the study analyzes how the national calendar functions as a temporal artifact that determines which events are institutionalized as shared memory. Research findings indicate that the distribution of national holidays and collective leave days reveals a pattern of religious time dominance, particularly through the greater representation of majority religious celebrations. The article contributes to the study of state-religion relations by expanding the understanding of hegemony as a form of temporal control, specifically, how the state constructs legitimacy and collective identity through the regulation of social time. The study asserts that the national calendar is not merely an administrative list but a political space reflecting processes of inclusion, exclusion, and the negotiation of religious representation within a pluralistic society.